Between Eagle and Dragon: Affective representations of the United States and China in South Korean Media - Seungwoo Han (PLoS ONE, 2026)
Emotions are closely implicated in how states are represented and interpreted. This study examines the affective dimensions of South Korean media portrayals of the United States and China from 1992 to 2025, focusing on variation in evaluative tone and emotional intensity. Drawing on theories of affective framing and media agenda-setting, the analysis traces long-term patterns in valence and arousal using a large corpus of newspaper articles and a computational text analysis approach. The results indicate a persistent asymmetry. Coverage of the United States remains relatively stable, with moderately positive evaluations and low levels of emotional intensity, whereas portrayals of China become more negative and more affectively charged over time. These differences appear as sustained patterns rather than isolated fluctuations and are consistent with broader features of South Korea’s geopolitical context, including alliance relations, historical memory, and media environments. By documenting these patterns, this study contributes to the analysis of affect in media discourse and provides a framework for examining how major powers are represented in national contexts over time.